The Urgency of Regulating Asset Recovery at the District Attorney Level to Ensure the Exclusionary Rules Principle in Corruption Crimes - Fredi Wahyu Putra Adhyaksa; Prija Djatmika; Fachrizal Afandi (IBLAM LAW REVIEW, 2026)
Corruption is categorized as an extraordinary crime that requires extraordinary measures. One important strategy is asset recovery to compensate for state losses. However, the absence of explicit regulations regarding the principle of exclusionary rules in Indonesian positive law has caused disharmony between theory and practice. Purposes of the Research: This study aims to analyze the implications of asset recovery regulations on the application of exclusionary rules in the enforcement of criminal acts of corruption. Methods of the Research: This study uses a normative juridical method with a legislative and conceptual approach, focusing on the analysis of regulations and the authority of the District Attorney's Office related to asset recovery. Results / Main Findings / Novelty/Originality of the Research:The results of the study show that the lack of regulations and SOPs at the District Attorney's Office level has the potential to weaken the legitimacy of law enforcement. This condition emphasizes the need for comprehensive regulations that explicitly include the principle of exclusionary rules. In addition, the establishment of an Asset Recovery Section in the District Attorney's Office is necessary to ensure effectiveness, legal certainty, and justice in combating corruption.